Animations to communicate public health prevention messages: a realist review protocol - McCorry, Kathleen; Maniatopoulos, Gregory; Errington, Linda; Land, Ellie; Craig, Michael; Vijaykumar, Santosh; Bärnighausen, Till; O'Brien, Nicola (BMJ open, 2024)
Introduction With digital and social media advances, animated health communications (health animations) are highly prevalent globally, yet the evidence base underpinning them remains unclear and limited. While individual studies have attempted to explore the effectiveness, acceptability and usability of specific features of health animations, there is substantial heterogeneity in study design, comparators and the animation design and content. Consequently, there is a need to synthesise evidence of health animations using an approach that recognises this contextual complexity, which may affect their impact. - Methods and analysis This project aims to understand why, how, for whom, to what extent and in which contexts health animations are expected to promote preventive health behaviours. We will conduct a realist review following Pawson’s five iterative stages to (1) define the review scope and locate existing theories; (2) search for evidence; (3) select and appraise evidence; (4) extract data and (5) synthesise data and refine theory. Engagement with stakeholders involved in developing, testing, implementing or commissioning health communications, including animations, will allow the initial programme theory to be tested and refined. The findings will be reported in accordance with Realist and Meta-narrative Evidence Syntheses: Evolving Standards. - Ethics and dissemination Ethical approval for the public stakeholder work was provided by the Northumbria University Research Ethics Committee. We will disseminate the findings widely through outputs tailored to target specific professional, public and patient audiences. Dissemination will occur through stakeholder engagement as part of the research, a peer-reviewed publication and conference presentations. - PROSPERO registration number CRD42023447127.